An Analysis of Imperatives in Grade X English Textbook - Wahyuningtyas, Dwi (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2025)
The Grade X English textbook uses the PPP (Presentation, Practice, Production) method to teach imperatives. This method shows how to introduce, reinforce, and use this grammatical feature. The PPP framework provides the contextual elucidation of imperatives, succeeded by organized practice activities and culminating in autonomous production. In this case, students write their own sentences employing the target structure. This study analyzes the treatment given to imperatives in the textbook within this framework. A descriptive qualitative methodology was employed, with data gathered through content analysis of the textbook. The results show that the textbook makes grammatical explanations as easy as possible for students at different levels of proficiency, which helps them learn and improve their skills over time. In particular, imperatives are taught through clear examples and conversations in context, followed by guided exercises and activities that encourage communication. This method provides people with a way to internalize the structure slowly. The research demonstrates that utilizing the PPP method in the instruction of imperatives enhances student comprehension and exemplifies effective grammar teaching in EFL materials. These findings are crucially important for textbook authors and educators, highlighting the importance of scaffolding grammar instruction according to learners' readiness, which promotes active language use.